Perception of innovativeness in companies and business environment institutions - Misterek, Wojciech (Management, 2014)
The aim of this paper is to present key features of innovative enterprise in opinion of entrepreneurs and Business Environment Institutions. The survey conducted among entities from selected eu region reveals how innovativeness is described by entrepreneurs and institutions which supporting them. It appears that the key feature of an innovator is ability to quickly adapt to market changes by modifying offered products and processes. The significant problem, identified by the survey, is insufficient cooperation between entrepreneurs and universities/research centres. According to this, it is indispensable to create adequate mechanisms, which on the one hand would activate academic world to commercialize their research and on the other hand improve the research information flow.
Keywords: inovativnost; podjetja; podjetništvo; poslovno okolje; raziskave; raziskovalno delo